An exploratory, randomised, crossover study to investigate the effect of nicotine on cognitive function in healthy adult smokers who use an electronic cigarette after a period of smoking abstinence - Harry J. Green; Olivia K. O’Shea; Jack Cotter; Helen L. Philpott; Nik Newland (Harm Reduction Journal, 2024)
Abstract Background As well as being associated with serious negative health outcomes, smoking has been reported to have an array of physiological and psychological effects, including effects on mood and cognitive function. Post-cessation, loss of such effects (including temporary deficits in cognitive function) have been cited as reasons for resumption of smoking. The effects of e-cigarettes and nicotine delivered by e-cigarettes on these functions have not been widely researched but may play a role in the effectiveness of e-cigarettes as a satisfactory alternative to combustible cigarettes for people who smoke, and in encouraging individuals who would otherwise continue to smoke, to transition to e-cigarettes. Methods The study was an exploratory, randomised, partially-blinded, single-centre, five-arm crossover trial that recruited 40 healthy male and female people who smoke. At 5 study sessions, following a 12-h period of nicotine abstinence, participants were randomly assigned to use either a combustible cigarette, an e-cigarette of three varying nicotine strengths (18 mg/mL, 12 mg/mL or 0 mg/mL respectively) or observe a no product usage session. Participants completed pre- and post-product usage assessments to examine the product usage effect on cognitive performance (using the Cambridge Neuropsychological Test Automated Battery (CANTAB)), subjective mood and smoking urges. Results A significant improvement in sustained attention task performance was observed following use of both the nicotine containing e-cigarettes and combustible cigarette compared to no product use. Additionally, there were no significant differences between the nicotine containing products, indicating that nicotine use enhanced sustained attention regardless of delivery format. Nicotine containing e-cigarette and combustible cigarette use also significantly improved overall mood of participants compared to no product use, with no significant differences observed between the nicotine containing products. Nicotine containing e-cigarette and combustible cigarette use significantly reduced smoking urges compared to no product use, though combustible cigarette use elicited the greatest reduction in smoking urges. Conclusions Overall, the nicotine containing products improved sustained attention and mood while reducing smoking urges, with the studied e-cigarettes having comparable effects to combustible cigarettes across the assessed cognitive parameters and mood measures. These results demonstrate the potential role of e-cigarettes to provide an acceptable alternative for combustible cigarettes among people who would otherwise continue to smoke. Trial registration ISRCTN (identifier: ISRCTN35376793).